MEMBACA PIKIRAN MANUSIA: ANALISIS SISI NEGATIF PIKIRAN MANUSIA KAITANNYA DENGAN PENYAKIT TUBUH - mulyana mulyana (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2016)
Human mind is the first source for health, and the sickness of body is originated from his own mind. What is mean by this mind? Thinking positively will cause human body to be health, and thinking negatively will cause human body to be sick.